Mast cell stabilizer disodium cromoglycate improves long-term cognitive impairment after general anesthesia exposure in neonatal mice - Zhang, Xiaojun; Wu, Wensi; Zheng, Zhenzhen; Li, Liang; Chen, Junjun; Zhong, Junying; Zhao, Le; Chen, Jiawei; Wang, Zhi; Meng, Fanqing (Frontiers in Neuroscience, 2022)
Background Prolonged exposure to general anesthesia (GA) results in long-lasting cognitive impairment, especially during critical stages of brain development. An exaggerated neuroinflammation induced by anesthesia is generally considered to be a key cause of cognitive impairment. Methods Postnatal day 7 (PND 7) mice were exposed to GA by isoflurane inhalation for 6 hours or mock anesthesia. Disodium cromoglycate (DSCG) was intraperitoneally injected daily for 2 weeks, beginning from 30 minutes before anesthesia. The post-anesthesia evaluation included behavioral tests, toluidine blue staining, immunofluorescence and western blot. Results Our results demonstrated the long-term cognition were impaired after 6 hours GA exposure in neonatal mice. DSCG treatment ameliorated early mast cells (MCs) degranulation and mast cell tryptase (MCT) expression, which helps to attenuate subsequent neuroinflammation, activation of microglia and astrocytes, and damage to oligodendrocytes and synapses to improve cognitive impairment. Conclusion DSCG could effectively improve long-term cognitive impairment after GA exposure in neonatal mice.